Evaluation of simplified methods of analysis for structures with triple friction pendulum isolators. - Fadi, Fabio (Earthquake engineering & structural dynamics.)
Triple friction pendulum isolators, that exhibit behavior with amplitude-dependent strength and instantaneous stiffness, represent a new development in seismic isolation. The application of simplified methods of analysis for this type of seismically isolated structures requires development of tools of simplified analysis and demonstration of their accuracy. This paper describes these tools and presents validation studies based on a large number of nonlinear response history analysis results. It is shown that simplified methods of analysis systematically provide good and often conservative estimates of isolator displacement demands and good estimates of isolator peak velocities.